Innovation and Performance of Small and Medium Enterprises in Kabale Municipality, Uganda. - Ben, Atuheire (Kabale University, 2020)
Innovation plays an important role in the performance and growth of SMEs as it leads a firm to gain competitive advantage over others, gain market share and increase customer satisfaction as well as profitability and sales growth. This study investigated the relationship between innovation and performance of Small and Medium Enterprises (SMEs) in Kabale Municipality. The objectives of the study were; to examine the relationship between innovation and SME performance, to explore strategies being used by SMEs to be more innovative and to analyze the constraints facing innovation strategies for effective performance in Kabale Municipality. Kabale Municipality SMEs were selected for the study because the Municipality is in the heart of Kabale district where most businesses are concentrated and this made it easier to conduct the study. The study employed a cross sectional survey design which is analytical in nature because it is employed in research to gather data about phenomenon (innovation and performance) at one specific point in time depending on the nature of the study, covered 162 SMEs. The results indicated that there was a significant positive relationship between innovation and SME performance, that access to funds was the leading challenge to SME innovation and that process innovation strategies were being engaged by SMEs in KMC. It concluded that all SME operators in the study area realize the importance of innovation in the growth of their businesses, found innovation being a significant predictor of SME performance. Therefore, the study recommended managements of the different SMEs to welcome innovation in their work processes as this will improve on their firm performances and also their competitive advantage. The study also recommended administrators to table matters affecting SMEs into management meetings to provide an enabling environment especially for the starter SMEs. Finally the study also recommended the need for training of SME operators in K.M.C by Kabale Municipality administration in collaboration with private sector foundation aimed at equipping SME operators with business skills.